Stability study of rock slope in fractured quartzite at right side of spillway, Middle Marsyangdi Hydroelectric Project, Nepal - Nepal, Kaustubh Mani; Olsson, Roger (Journal of Nepal Geological Society, 2003)
A 120 m long and 68 m high rock cut slope is designed at the right side of spillway of Middle Marsyangdi Hydroelectric Project. This paper describes the stability studies performed for the rock cut slopes in jointed quartzite for foundation of spillway.